2010
DOI: 10.1186/1477-5956-8-10
|View full text |Cite
|
Sign up to set email alerts
|

Proteome characterization of cassava (Manihot esculenta Crantz) somatic embryos, plantlets and tuberous roots

Abstract: BackgroundProteomics is increasingly becoming an important tool for the study of many different aspects of plant functions, such as investigating the molecular processes underlying in plant physiology, development, differentiation and their interaction with the environments. To investigate the cassava (Manihot esculenta Crantz) proteome, we extracted proteins from somatic embryos, plantlets and tuberous roots of cultivar SC8 and separated them by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 28 publications
(38 reference statements)
4
56
0
5
Order By: Relevance
“…Yet, there has not been any report in the literature on molecular and biochemical investigation of leaf genes or proteins involved in the tuberization process of the cassava plant. Particularly, to date, there have been very few papers in the literature report on proteomic analysis in cassava (Cabral and Carvalho 2001;Sheffield et al 2006;Li et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, there has not been any report in the literature on molecular and biochemical investigation of leaf genes or proteins involved in the tuberization process of the cassava plant. Particularly, to date, there have been very few papers in the literature report on proteomic analysis in cassava (Cabral and Carvalho 2001;Sheffield et al 2006;Li et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Cytokinins are a family of N 6 -substituted adenine derivatives whose stimulation of cell division and organogenesis in plants has been studied since the discovery of the kinetin (Miller et al 1956). Recently, Li et al (2010) revealed that 15 proteins involved in amino acid metabolism and photosynthetic activity are significantly expressed at earlier stages of shoot differentiation from organogenic callus. And numerous compounds related with sugar mobilization and nitrogen metabolism had important role in early stages of shoot differentiation .…”
Section: Resultsmentioning
confidence: 99%
“…Cassava provides edible leaves and tubers (Boansi, 2017;Li et al, 2010) and is produced almost *Corresponding author. E-mail: ibcuvaca@ksu.edu.…”
Section: Introductionmentioning
confidence: 99%